SISTEM INFORMASI APOTEK BUNDA PLUS - , ANISA RAHMANDHANI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Bunda Plus pharmacy as provider many kind of pharmaceutical product, had has a branch. In practically, including processing data of drugs and recording sales transactions has been using computer. Unfortunately, the system still does not optimally used because the data between pharmacies does not integrated yet into one system, so it can leads to data loss if something unwanted happens. Based on these problems, centralized online information system needed to manage overall data management activities between two branches. In order to optimize data management and transaction reports. Bunda Plus Pharmacy Information System is built using PHP programming language, CodeIgniter framework, and MySQL database. Intended, this system is able to improve the ease of data management process between pharmacies and generate reports that are available in the management module is able to handle search the availability of drugs in the pharmacy.